Performance assessment of ISO-5167 and symmetrical Venturi meters for measuring low Reynolds number turbulent incompressible isothermal flow - Ahmad Sharifian; Keith Wells (International Journal of Thermofluids, 2024)
The selection of Venturis depends on the desired flow measurement sensitivity, permanent pressure loss, discharge coefficient, and relative pressure loss coefficient. The ISO-5167 standard specifies geometries for Venturi metres within the Reynolds number range of 200,000 to 2,000,000. This study evaluates the performance of ISO-5167 and six suggested symmetrical Venturis operating in both unidirectional and bidirectional flow conditions for flows with Reynolds numbers below 200,000. The performance of ISO-5167 and six suggested symmetrical Venturis with β-ratios of 0.4 and 0.55, and cone angles of 10°, 20°, and 40° degrees were evaluated. The study found that the ISO-5167 Venturi performed best in the conventional flow direction for flows with Reynolds numbers greater than ≈34,000. The symmetrical Venturi meter with a β-ratio of 0.55 and a cone angle of 10° (SVD4) exhibited performance comparable to the ISO-5167 Venturi for the conventional flow direction. The ISO-5167 Venturi exhibited a significant flow reversal when operating in the opposite direction to the conventional flow. The SVD4 Venturi metre demonstrated the potential to save 71 % of energy in the reverse flow direction compared to the ISO-5167 Venturi, suggesting an energy saving of up to 43 % in certain bi-directional flow scenarios.